2017
DOI: 10.2147/hp.s141283
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory muscle dysfunction in animal models of hypoxic disease: antioxidant therapy goes from strength to strength

Abstract: The striated muscles of breathing play a critical role in respiratory homeostasis governing blood oxygenation and pH regulation. Upper airway dilator and thoracic pump muscles retain a remarkable capacity for plasticity throughout life, both in health and disease states. Hypoxia, whatever the cause, is a potent driver of respiratory muscle remodeling with evidence of adaptive and maladaptive outcomes for system performance. The pattern, duration, and intensity of hypoxia are key determinants of respiratory mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 111 publications
(212 reference statements)
0
15
0
Order By: Relevance
“…However, in our view, the cautionary tone espoused in the original article is over‐stated, and distracts from the commendable work of the authors revealing impressive effects of antioxidant intervention in the dystrophin‐deficient mdx mouse model of Duchenne muscular dystrophy. By way of disclosure, our group advocates antioxidant intervention for respiratory muscle dysfunction in respiratory disease, on the basis of observations in several rodent models of hypoxia (reviewed in O'Halloran & Lewis, ). Moreover, we have reported that N ‐acetylcysteine (NAC) is the most effective antioxidant in preventing respiratory muscle weakness and fatigue following exposure to chronic sustained hypoxia (Lewis et al .…”
mentioning
confidence: 99%
“…However, in our view, the cautionary tone espoused in the original article is over‐stated, and distracts from the commendable work of the authors revealing impressive effects of antioxidant intervention in the dystrophin‐deficient mdx mouse model of Duchenne muscular dystrophy. By way of disclosure, our group advocates antioxidant intervention for respiratory muscle dysfunction in respiratory disease, on the basis of observations in several rodent models of hypoxia (reviewed in O'Halloran & Lewis, ). Moreover, we have reported that N ‐acetylcysteine (NAC) is the most effective antioxidant in preventing respiratory muscle weakness and fatigue following exposure to chronic sustained hypoxia (Lewis et al .…”
mentioning
confidence: 99%
“…Oxidative stress is a recognized feature of respiratory disorders including DMD. Targeting oxidative stress within muscle by reducing the bioavailability of ROS or boosting endogenous antioxidant stores are attractive adjunctive therapies, particularly in conditions where redox imbalance presents and contributes to muscle pathology [20,21]. We have previously demonstrated that administration of a superoxide scavenger (Tempol) to mdx mice for two weeks restores metabolic enzyme activities and improves diaphragm muscle force-generating capacity [22].…”
Section: Introductionmentioning
confidence: 99%
“…Acute exposure to hypoxia can enhance diaphragm fatigue. There are reports of greater hypoxic tolerance in respiratory muscles of female rodents, purportedly as a result of the protective effects of oestrogen, particularly relevant to chronic exposure to hypoxia in the context of disease (O'Halloran & Lewis, 2017). In this issue of The Journal of Physiology , Archiza et al .…”
mentioning
confidence: 99%
“…The hypoxic tolerance in men is curious given that a substantial enhancement of male diaphragm fatigue during hypoxia has been reported elsewhere (Verges et al . 2010). The difference may relate to temporal responses in acute hypoxia because Verges et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation